2023
DOI: 10.1038/s41467-023-38611-5
|View full text |Cite
|
Sign up to set email alerts
|

Durvalumab plus tremelimumab for the treatment of advanced neuroendocrine neoplasms of gastroenteropancreatic and lung origin

Abstract: Single immune checkpoint blockade in advanced neuroendocrine neoplasms (NENs) shows limited efficacy; dual checkpoint blockade may improve treatment activity. Dune (NCT03095274) is a non-randomized controlled multicohort phase II clinical trial evaluating durvalumab plus tremelimumab activity and safety in advanced NENs. This study included 123 patients presenting between 2017 and 2019 with typical/atypical lung carcinoids (Cohort 1), G1/2 gastrointestinal (Cohort 2), G1/2 pancreatic (Cohort 3) and G3 gastroen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Patients with typical and atypical carcinoids (Lung NETs) demonstrated the highest overall response rate (ORR), with no statistically significant difference in progression-free survival (PFS) between the Lung NETs and other groups, such as gastrointestinal and pancreatic NETs. However, in terms of overall survival, patients with Lung NETs experienced a greater benefit than those in other study groups [ 76 ].…”
Section: Navigating Therapeutic Strategies: Efficacy In Treating Lung...mentioning
confidence: 99%
“…Patients with typical and atypical carcinoids (Lung NETs) demonstrated the highest overall response rate (ORR), with no statistically significant difference in progression-free survival (PFS) between the Lung NETs and other groups, such as gastrointestinal and pancreatic NETs. However, in terms of overall survival, patients with Lung NETs experienced a greater benefit than those in other study groups [ 76 ].…”
Section: Navigating Therapeutic Strategies: Efficacy In Treating Lung...mentioning
confidence: 99%
“…The FDA has approved the treatment of multiple tumor types, including melanoma, non-small cell lung cancer, head and neck squamous cell carcinoma, and urothelial cancer. A previous study has suggested that poorly-differentiated gastrointestinal NENs, mismatch repair deficiency, or microsatellite instability are indications for ICB [ 135 ].…”
Section: Management Of Gep-nensmentioning
confidence: 99%
“…PD-L1 expression by combined positive score (CPS) did not correlate with treatment activity. In analyzed patients, no microsatellite instability (MSI)-high status was reported [ 71 ].…”
Section: Therapeutic Approach To Upo-nenmentioning
confidence: 99%